Cyber and Maritime Drone Threats: The Future of National Maritime Security - Legowo, Endro; Hilmansyah, Ceppi; Yulianto, Bayu Asih; Prakoso, Lukman Yudho; Risahdi , Muhammad (Jurnal Indonesia Sosial Sains, 2025)
This study analyzes cyber threats and the use of marine drones in the context of national maritime security. As illegal activities and potential conflicts increase in Indonesian waters, drone technology and cyber defense systems are becoming important instruments to improve surveillance, early detection, and rapid response. This study uses a descriptive qualitative approach based on the analysis of documents, literature, and official secondary data. The results show that the integration of marine drones and cyber defense increases patrol effectiveness by up to 40% and reduces the risk of territorial violations and piracy. This research emphasizes the need for a holistic strategy to deal with future maritime challenges.